Prebiotic, probiotic and marine algae suplementation in juvenile tilapia diet - Ranzani-Paiva, Maria José T.; de Carla Dias, Danielle; Cavalcante, Raissa Bertoncello; Telli, Guilherme; Oshiro, Eliana [UNESP]; Ishikawa, Carlos Massatoshi; Petesse, Maria Letizia; Fernandez-Alarcon, Miguel Frederico; Natori, Mariene Miyoko; Moriñigo, Miguel Angel; Tapia, Silvana; Hamed, Said Ben; et al. (Boletim do Instituto de Pesca, 2024)
This study aimed to evaluate the probiotic mannan oligosaccharide (MOS), and marine algae for Nile tilapia juveniles (Oreochromis niloticus) feeding. The parameters analyzed were fish-growth rate, hematological and immunological parameters, and intestinal microbiota. Also, the fish were submitted to experimental infection challenge with Aeromonas hydrophila to evaluate the immune response. Nile tilapia juveniles (mean weight 8.86 ± 3.22 g) were used in the six treatments with four replicates, for 63 days. The treatments were: control with basal diet; PAS-TR: basal diet plus 0.04 g·kg-1 of the probiotic (Bacillus cereus and Bacillus subtilis); MOS: basal diet plus 4 g·kg-1 of the prebiotic mannooligosaccharide, 4 g·kg-1 of the prebiotic Kappaphycus alvarezii. Two more diets were formulated by a combination of PAS-TR + MOS (4 +4 g·kg-1), and PAS-TR + KAP (4 +4 g·kg-1). For the challenge experiment, the fish were fed for 21 days, infected via intraperitoneal injection with A. hydrophila (1 x 106 UFC·mL-1), and the mortality rate was registered for 15 days post-infection. Results indicated the capacity of probiotic to remain in the gut for 63 days, and it was inhibited neither by autochthonous microbiota nor by prebiotics used. The feed additives tested for Nile tilapia did not cause a beneficial or adverse effect on growth or hematological variables evaluated. However, these treatments protected the fish from A. hydrophyla infection, proved by higher survival rate, and relative protection levels. We concluded that probiotic PAS-TR and prebiotics MOS and KAP, combined or not as symbiotics, may promote immune protection and reduce the mortality rate of A. hydrophyla infection.
Suplementação de prebióticos, probióticos e algas marinhas na dieta de tilápia juvenil
Keywords: Aeromonas hydrophila; Aquaculture; Hematology; Immunostimulants; Nutrition; Symbiotics